Pengaruh Discovery Learning Terhadap Hasil Belajar Siswa Kelas VII Pada Mata Pelajaran Pendidikan Agama Islam - Meiyanda, Rana; Mahardika, Mutiara; Ashabul Jannah, Wahyu; Amrullah; Sholihin (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study investigates the effectiveness of the Discovery Learning model in improving students’ learning outcomes in Islamic Jurisprudence (Fikih), particularly the topic of salat, among seventh-grade students at SMPN 29 Rejang Lebong. A quasi-experimental pretest–posttest control group design was employed involving 40 participants assigned to experimental and control groups. Data were collected through cognitive tests, classroom observations, and documentation, and analyzed using an independent t-test to examine differences in mean scores. The Discovery Learning stages stimulation, problem identification, data gathering, verification, and conclusion—were implemented in the experimental group. Results indicate a statistically significant improvement in the experimental group compared to the control group (p < 0.05), demonstrating the model’s effectiveness in strengthening students’ conceptual understanding of salat. The findings imply that PAI teachers should integrate discovery-based approaches to enhance instructional quality. Future studies are encouraged to explore affective and psychomotor aspects of worship practices. The article includes tables, graphs, and supporting instruments.